In the Land of the Eastern Queendom The Politics of Gender and Ethnicity on the Sino-Tibetan Border - Jinba, Tenzin (Studies on Ethnic Groups in China, 2013)
Open-access edition: DOI 10.6069/9780295804842 The story underlying this ethnography began with the recent discovery and commercialization of the remnant of an ancient "queendom" on the Sichuan-Tibet border. Recorded in classical Chinese texts, this legendary matriarchal domain has attracted not only tourists but the vigilance of the Chinese state. Tenzin Jinba's research examines the consequences of development of the queendom label for local ethnic, gender, and political identities and for state-society relations.